A study to evaluate the attitude of faculty members of public universities of Pakistan towards shared governance - Shah, Shakeela; Yousuf Zai, Sajid; Munshi, Parveen; Asimiran, Soaib; Lope Pihie, Zaidatol Akmaliah; Ahmad, Shamsuddin (International Institute for Science, Technology & Education, 2014)
This paper is based on the evaluation of the attitude of faculty members toward shared governance. Four indicators were used for share governance: role of dean, role of faculty, role of board, and role of joint decision making. Five points liker scale questionnaire of Baker-Brown was used in this study. There were 90 samples for this study from all public universities of Pakistan. Two research questions were formulated for this study. A multivariate analyses of variance (MANOVA) approach was used to answer research questions. SAS 9.3 software used to analyze the data. A one-way MANOVA result indicates that there is a significant difference in the perception of shared governance in all four indicators by the faculty rank group at a=0.05 since F (12, 219.89) = 4.68, p <. 001 correspondence to Wilks’ ? = .548, partial eta squared = .182. Power to detect the effect was .99. There is 55% of variance for shared governance perception is accounted by faculty position. The gender group one-way MANOVA result also indicates that there is a significant difference in the perception of shared governance in all four indicators by gender group at a=0.05 since F (4, 85) = 5.97, p <. 001, correspondence to Wilks’ ? = .781, partial eta squared = .182. Power to detect the effect was .99. There is 55% of variance for shared governance perception is accounted by faculty position. Follow-up tests indicates that there was a significance difference in the dean role and join decision making role indicators of shared governance according to the faculty position. There was also significance difference found in the overall MANOVA when analyzed by gender group since Wilks’ ? = .781, F (4, 85) = 5.97, p <. 001, partial eta squared = .219. Power to detect the effect was .98. The result shows that there was 22% of variance for shared governance perception is accounted by male and female group.